1996
DOI: 10.1080/02652039609374439
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intakes of nitrate, nitrite and NDMA in the Finnish mobile clinic health examination survey

Abstract: Concern about potential health hazards of nitrate, nitrite and N-nitroso compounds necessitates calculations of exposures to these compounds and their distribution in normal populations. This study describes dietary intake of nitrate (NO3-), nitrite (NO2-) and N-nitrosodimethylamine (NDMA) among 5304 adult men and 4750 women, who participated in the Finnish Mobile Clinic Health Examination Survey in 1967-72. Food consumption data for each individual over the preceding year were collected by a dietary history i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 21 publications
5
71
0
4
Order By: Relevance
“…On the other hand, foods with a high content of NDMA 11 , such as smoked or salted fish, are not important contributors to the total intake because they are consumed by a very low percentage of the EPIC -Spain population (0.30% and 3%, respectively). Different patterns of consumption have been found in studies published in Finland and France, in which smoked fish contributed 22 -25% to total intakes of NDMA 18,33 . The highest values of NDMA intake have been reported in Japan, due to high intakes of dried and smoked fish 34 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, foods with a high content of NDMA 11 , such as smoked or salted fish, are not important contributors to the total intake because they are consumed by a very low percentage of the EPIC -Spain population (0.30% and 3%, respectively). Different patterns of consumption have been found in studies published in Finland and France, in which smoked fish contributed 22 -25% to total intakes of NDMA 18,33 . The highest values of NDMA intake have been reported in Japan, due to high intakes of dried and smoked fish 34 .…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question whether information at the food level as an indicator of cured PM consumption is sufficient to describe exposure differences for nitrite/nitrate through PM consumption, because this approach assumes a similar NaNO 2 content in the ready-to-eat PM products in the different countries which might not be correct. In a Finnish study, conducted between 1966 and 1972, mean intake of nitrite was 5.3 mg day 21 , provided nearly exclusively by cured meats and PM 5,36 . However, another report from Finland calculated an average daily intake of 1.88 mg 33 .…”
Section: Table 2bmentioning
confidence: 99%
“…Some studies have also reported the presence of nitrite in other foodstuffs, e.g. cereals, cheese and bread, but the content of nitrite in these food groups is often lower than the limit of detection (LOD) (Knight et al 1987;Dich et al 1996;Petersen & Stoltze 1999;Jakszyn et al 2006;Thomson et al 2007;Menard et al 2008;Griesenbeck et al 2009). …”
mentioning
confidence: 99%
“…Furthermore, nitrate is found in cured meat, either through F o r P e e r R e v i e w O n l y being used as a food additive or formed from conversion of initially added nitrite. Nitrate is also present in limited amounts in other foodstuffs such as bread, cereals and dairy products (Dich et al 1996;Ysart et al 1999;Menard et al 2008;Griesenbeck et al 2009 The conversion of nitrate to nitrite in the body mainly takes place in the oral cavity, and it has been estimated that 5-7% of nitrate ingested is converted to nitrite by bacteria normally occurring in the mouth (Eisenbrand et al 1980;FAO/WHO 2003b 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 years, 713 school children aged 8-9 years and 956 school children aged 11-12 years, resulting in a total of 2259 children. The children aged 4 years were randomly selected from a register of families with children of this age, while the school children were randomly selected as whole school classes.…”
mentioning
confidence: 99%